(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE "HUMAN RESOURCES AND MODERN PROFESSIONS IN THE WORLD" – Aachen, Germany, 2024)
At the present time, the most relevant research in thoracic surgery in the world continues to be the development and implementation of alternative methods of aerostasis during resection interventions and decortication.Thoracic surgeons often encounter postoperative air leaks, atelectasis, and pneumonia as common complications of lung resection. In most cases, they are treated correctly, which avoids serious consequences. However, some clinical conditions that initially manifest as general complications may become severe if the correct differential diagnosis is not made at an early stage.The relevance and great practical significance of developing issues of persistent aerostasis is determined not only by the high frequency of its occurrence, but also by the difficulties in choosing the optimal method for completely sealing the lungs. Further research in this direction will undoubtedly improve the modern understanding of the capabilities of implants and will allow us to study the problem of aerostasis from new positions in thoracic surgery.